Studying the Effect Addition of Okra-Natural Mucilage as Drag Reducing Agent in Different Size of Pipes in Turbulent Water Flowing System - Abdulbari, Hayder A.; R. M., Yunus; M. A., Ahmad (2009)
The problem of pumping power losses in pipelines carrying liquids and flowing in turbulent mode is one of the major challenges in the power saving field. Pumping power saving by the addition of minute quantities of additives to the main flow was applied in the present work. Natural drag reducing agent was prepared and extracted from okra fruit and it was tested in a closed loop of turbulence water flowing system. Flow tests were conducted using water as the carrying liquid. The experimental work starts by pumping water from reservoir tank that had mixed with mucilage was pumped with six different flow rates in two different pipe diameters (0.015, 0.025 m ID). The types of pipe used are galvanized iron pipe. The testing length of this flow system is 1.5 m. Objective to explain drag reduction differences between large and small pipes were successful. The results shows that, percentage drag reduction (Dr%) increases by increasing the concentration of Okra-Natural mucilage. Maximum Dr% of 71% was obtained using 1000 ppm of Okra- Natural Mucilage in water flow system.